1997
DOI: 10.1046/j.1365-3059.1997.d01-29.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative host reactions and Frankliniella occidentalis transmission of different isolates of tomato spotted wilt tospovirus from Spain

Abstract: The abilities of different isolates of tomato spotted wilt tospovirus (TSWV) collected from northeastern and eastern Spain to infect 10 host species, and to be acquired and transmitted by the western flower thrips (WFT), Frankliniella occidentalis were compared. Two isolates of TSWV from a single source plant could be separated according to the different type of local lesions they induced in Nicotiana glutinosa. Host ranges of the studied TSWV isolates were very similar, but differences were found in the sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0
7

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 20 publications
2
21
0
7
Order By: Relevance
“…Both direct and indirect effects of the pathogen on the vector, or vice versa, can be beneficial or harmful, depending on the species [1][4]. For example, studies of the indirect effects of viruses on their vectors have revealed a variety of outcomes, ranging from positive [2], [5][10], neutral [11], [12], to negative [13], [14]. While the effects of these interactions on individual pathogens and herbivores are often quantified, the consequences of these interactions for the population dynamics of both types of organisms and the evolution of ecological communities have rarely been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Both direct and indirect effects of the pathogen on the vector, or vice versa, can be beneficial or harmful, depending on the species [1][4]. For example, studies of the indirect effects of viruses on their vectors have revealed a variety of outcomes, ranging from positive [2], [5][10], neutral [11], [12], to negative [13], [14]. While the effects of these interactions on individual pathogens and herbivores are often quantified, the consequences of these interactions for the population dynamics of both types of organisms and the evolution of ecological communities have rarely been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, both the tospovirus species themselves and their various isolates also play an important role in determining the thrips vector competence (being viruliferous or non‐viruliferous) (Wijkamp et al. 1995; Roca et al. 1997; Nagata et al.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, virus induced physiological or morphological changes of the host plant will obviously affect choice behaviour and development as well as subsequent virus transmission by any thrips population (Wijkamp et al. 1995; Roca et al. 1997).…”
Section: Introductionmentioning
confidence: 99%
“…2004), through neutral effects (Wijkamp et al. 1996; Roca et al. 1997) to negative effects (Jensen 1959; DeAngelis et al.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies use only mechanical inoculations to infect the plants, thus preventing the induction of defences by the vector (Blua & Perring 1992; Bautista et al. 1995; Roca et al. 1997).…”
Section: Introductionmentioning
confidence: 99%